Two-Dimensional Photoacoustic/Ultrasonic Endoscopic Imaging Based on a Line-Focused Transducer - Pang, Weiran; Wang, Yongjun; Guo, Lili; Wang, Bo; Lai, Puxiang; Xiao, Jiaying (Frontiers in Bioengineering and Biotechnology, 2022)
Existing acoustic-resolution photoacoustic/ultrasonic endoscopy (PA/USE) generally employs a point-focused transducer for ultrasound detection, which is only sensitive in its focal region, thus the lateral resolution and sensitivity drop dramatically when the targets move far from its focus. Even if a dynamic focusing algorithm is applied, the sensitivity out of the transducer focus is still much lower than that in the focus in ultrasonic imaging mode. In this work, we propose an acoustic-resolution PA/USE with a line-focused transducer to realize automatic focusing. The line-focused transducer, in comparison to a point-focused transducer, has an emission sound field that is more uniform, and the original signal intensity and signal-to-noise ratio (SNR) of the front and rear targets are closer in the radial direction, which is beneficial for improving the uniformity of target signals in ultrasonic imaging. Sufficient numerical simulations and phantom experiments were performed to verify this method. The results show that our method can effectively improve the lateral resolution in the image’s defocused region to achieve automatic focusing and perfectly solve the defect of the target signal difference in the far-focus region in ultrasonic imaging, while also enhancing the image SNR and contrast. The proposed method in this paper lays foundations for the realization of photoacoustic/ultrasonic combined endoscopy with enhanced lateral resolution and depth of focus, which can potentially benefit a many of biomedical applications.